Early trauma management skills in Australian general practitioners. - Lopez, D; Hamdorf, J; Ward, A; Emery, J (2006)
BACKGROUND: General practitioners (GPs) have a role in the early management of major trauma in rural Australia. The Early Management of Severe Trauma (EMST) course fulfils their educational needs by providing skills for the systematic management of the seriously injured patient. However, with any skill there is a natural loss over time. This study surveyed GPs who have completed the EMST course to determine their confidence in trauma management. METHODS: A two-page survey was mailed in December 2004 to all GPs who had completed an EMST course from 1989 to 2004 and were currently residing in Western Australia. The survey consisted of background questions, open-ended questions regarding the EMST course and skills confidence ratings using visual analogue scales. The final sample size was 223. RESULTS: Response rate was 55%. GPs were least confident in carrying out diagnostic peritoneal lavage and cricothyroidotomy. They were most confident inserting i.v. cannulas and managing fluid replacement. Their confidence in some of these skills were related to the frequency of managing trauma patients but not to the interval since completing the EMST course. GPs found the systematic approach to trauma management and practical/procedural skills as the most relevant components of EMST. They felt that EMST could be improved with more accessible refresher courses and more practical/procedural skills. CONCLUSION: Most of these GPs were involved in rural hospital work where they may be required to manage seriously injured patients. They require regular refresher courses to maintain their confidence levels in treating seriously injured patients.